2018
DOI: 10.1097/igc.0000000000001229
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Lymphovascular Space Invasion in the Absence of Lymph Node Metastases in Early-Stage Endometrial Cancer

Abstract: Lymphovascular space invasion is an overall poor prognostic factor in T1N0 endometrial cancer. After adjusting for other factors, LVSI remains an independent risk factor for worse overall survival. Therefore, estimation of overall survival in patients with early-stage, node-negative endometrial cancer should take into account LVSI status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 14 publications
5
36
1
Order By: Relevance
“…Pulgar et al showed that the presence of LVSI was associated with reduced prognosis and a shorter survival rate [9]. Cusano et al analyzed the prognostic significance of LVSI in patients with (T1N0) node-negative surgically staged endometrial cancer, and showed that LVSI was an independent factor of risk for reduced overall survival (OS), as were age, histologic grade, and tumor stage [10]. A recent retrospective study showed that increased patient age, advanced tumor stage, increased tumor grade, and the presence of LVSI were negative prognostic factors for patient survival in= high-grade endometrial cancer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Pulgar et al showed that the presence of LVSI was associated with reduced prognosis and a shorter survival rate [9]. Cusano et al analyzed the prognostic significance of LVSI in patients with (T1N0) node-negative surgically staged endometrial cancer, and showed that LVSI was an independent factor of risk for reduced overall survival (OS), as were age, histologic grade, and tumor stage [10]. A recent retrospective study showed that increased patient age, advanced tumor stage, increased tumor grade, and the presence of LVSI were negative prognostic factors for patient survival in= high-grade endometrial cancer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published data dealing with the importance of lymphovascular space invasion (LVSI) in pT1N0 node‐negative patients has shown the 5‐year disease recurrence rate of 4.8% in lymph node negative and LVSI negative and 14.1% lymph node negative and LVSI‐positive patients ( P = 0.006) . The question arises whether these facts are caused by the low sensitivity of the standard tests used for the detection of metastatic involvement of SLNs or not.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published data dealing with the importance of lymphovascular space invasion (LVSI) in pT1N0 node-negative patients has shown the 5-year disease recurrence rate of 4.8% in lymph node negative and LVSI negative and 14.1% lymph node negative and LVSI-positive patients (P = 0.006). 23 The question arises whether these facts are caused by the low sensitivity of the standard tests used for the detection of metastatic involvement of SLNs or not. In our group of patients, the OSNA method detected a statistically significant higher number of positive lymph nodes, which would result in the classification of a statistically significant higher number of patients into higher FIGO stages, which would better correspond to the frequency of patients in whom the recurrence of the disease occurs in the early stage.…”
Section: Detection Of a Sentinel Lymph Node In Ec Patients Is Not Amentioning
confidence: 99%
“…It is well stablished [30, 31] that the presence of LVSI is a potent predictor of lymph node metastasis. Even more, it is a powerful prognostic factor, even in the patients with no lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%